If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+(-4x)=22
We simplify the equation to the form, which is simple to understand
2x+(-4x)=22
Remove unnecessary parentheses
+2x-4x=+22
We move all terms containing x to the left and all other terms to the right.
+2x-4x=+22
We simplify left and right side of the equation.
-2x=+22
We divide both sides of the equation by -2 to get x.
x=-11
| 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= | | 17-13=2(x-6) | | 2u^2+2v^2+4=0 | | (2x-6)=28 | | 5(3c-1)-2=12c+2 |